A Case of Systemic Lupus Erythematosus Presenting as Guillain-Barré Syndrome - Okoh, Helen Chioma (Case Rep Rheumatol, 2015)
Systemic lupus erythematosus (SLE) is an autoimmune systemic disease with multiple organ involvement with high morbidity and mortality rate. Among the severe potential fatal complications are those of the central and peripheral nervous system which usually develop during the course of the disease and very rarely from the outset of the disease. We are reporting a rare case of Miller-Fisher (MFS) variant of Guillain-Barré syndrome (GBS) as the first manifestation of SLE in a 41-year-old female who progressed to flaccid paralysis with no neurological improvement with initial immunosuppressive therapy, plasmapheresis, and first cycle of intravenous immunoglobulin (IVIG) but with remarkable and complete recovery after the second 5-day course of IVIG.